Efficacy of neurofeedback training on sensory, cognitive awareness and behaviour among autism spectrum disorder (ASD) children and young adults - Nurul 'Atiqah, Binti Mustafa Kamal. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The research aims to evaluate the efficacy of neurofeedback training on their sensory, cognitive awareness, and behavior among autism spectrum disorder (ASD) children and young adults using the A TEC developed by Bernard Rimland and Stephen M. Edelson from Autism Research Institute. 34 participants were purposely selected fromKuching Autism Association (KAA). A quasi experimental study using pre test and post test design (within subjects) was conducted in an average of 24 sessions for ASD children. The three major steps in the treatment protocols used for the training were Delta, followed by Alpha and Beta training. There were series of observations for each participant before training and a series of observations after the training within the duration of six months study. Most ASD children lacked sensory, cognitive awareness and behavior. The children were characterized with hyperactive symptoms, lack of motor fine and lack of cognitive. A TEC score showed positives improvement in terms of sensory, cognitive awareness and behaviour. Paired Sample t-tests indicated statistical significant overall improvement in Autistic children (t (34) =9.122, P =0.000) who received NFT using the three steps treatment protocol as indicat~d by ATEC scores taken before and after the training. Other major findings in core ASD symptomatology includes a significant difference in weightage scores in sensory and cognitive awareness (t (34)=4.865,P=0.000), behavioral/health t(33)=2.03.p=0.000). Positive treatment outcomes could be associated with the reduced cerebral hyperconnectivity resulted from the three treatment protocols such as delta to inhibit the beta frequency, followed by· Alpha training for relaxation and finally Beta protocol to help the children focus. Protocols included primarily sequential (bipolar) or interhemispheric montages individualized for each participant. Our treatment experience is showing remarkable improvements in the participant's cognitive, sensory and behavior.